Exploring young children’s geometrical strategies - Gagatsis, Athanasios; Elia, Iliada; Modestou, Modestina; Sriraman, Bharath (NOMAD Nordic Studies in Mathematics Education, 2006)
This study explores young children’s strategies while transforming polygons, through the use of geometrical models. Data were collected from 291 children ranging from 4 to 8 years of age in Cyprus. Children were asked to draw a stairway of specific polygons, with each shape being bigger or smaller than its preceding one. Relationships between children’s responses in the transformation tasks, their ability to recognize geometric shapes and their IQ level were investigated. Results showed that children used three alternative strategies in the transformation tasks. Children’s IQ score was directly associated with their transformation strategies, while only a low recognition ability was associated with the use of a defective strategy.